EXPLORATION OF GLOBAL LEADERSHIP IN BUILDING EMPLOYEE ENGAGEMENT IN MULTINATIONAL COMPANIES IN BEKASI CITY - Sumarsid Sumarsid (Yayasan Education and Social Center, 2026)
This study aims to explore the role of global leadership and organizational culture in building employee engagement in multinational companies in Bekasi City. The approach used was qualitative with exploratory descriptive methods. Data were collected through in-depth interviews, observations, and documentation, then analyzed using NVivo software to identify key themes. The results showed that adaptive, communicative, and participatory global leadership can increase employee trust and engagement. In addition, an inclusive, collaboration-oriented organizational culture that upholds the value of integrity has proven to be an important factor in creating a conducive work environment. This study also found a synergy between global leadership and organizational culture in strengthening employee engagement, both emotionally, cognitively, and behaviorally. However, there are still challenges in implementation that are not evenly distributed across all levels of the organization. Therefore, companies need to develop an integrated strategy by strengthening cross-cultural leadership and internalizing organizational values. This study provides theoretical and practical contributions to the development of human resource management in multinational companies.